Improving Quality Using The Kano Model in Overcoming Competition in The Service Industry - Meri Andriani; Heri Irawan; Nanda Rizqa Asyura (International Journal of Engineering, Science and Information Technology, 2021)
The tight competition in the service industry, especially hospitality, has caused hoteliers to strive to improve service quality. Improving the quality of service is carried out in various ways, one of which is increasing the occupancy rate of hotel rooms. This is different from Hotel X. Hotel X is an old hotel located in Langsa which has experienced a decrease in room occupancy from time to time. The decrease was caused by the service from hotel X that was still not satisfactory to customers. The purpose of this study is to identify customer dissatisfaction with the quality of hotel services and provide design proposals to improve service quality. The method used in this study is the Kano model, which is the model used to identify customer satisfaction, through questionnaires given to customers, statistical tests are used to conduct adequacy tests and data uniformity tests for questionnaire data obtained. Excel and SPSS software are used in statistical tests, Minitab 16 software is used in making coefficient diagrams of customer satisfaction levels. Results and Discussion obtained 21 attributes in the must be a category, 8 attributes in the one-dimensional category, 2 in the attractive category, and 2 in the indifferent category, the attributes which are categorized as one dimensional, attractive, and must be are attributes that are prioritized to improve service quality. In conclusion, 31 attributes are included in customer dissatisfaction with hotel X, one of which is the physical condition of the building with a dissatisfaction value of -3,080. There are 18 attributes as proposed designs in improving service quality, five of which are adding and completing service-related equipment, infrastructure improvement, improvement and development of standard operating procedures (SOP), periodic maintenance and replacement of service support equipment, procurement of housekeeping equipment, cleaning of facilities. and infrastructure, installation of signs, warnings, and information.